2016
DOI: 10.1038/ng.3588
|View full text |Cite
|
Sign up to set email alerts
|

Population genomics studies identify signatures of global dispersal and drug resistance in Plasmodium vivax

Abstract: Plasmodium vivax is a major public health burden, responsible for the majority of malaria infections outside Africa. We explored the impact of demographic history and selective pressures on the P. vivax genome by sequencing 182 clinical isolates sampled from 11 countries across the globe, using hybrid selection to overcome human DNA contamination. We confirmed previous reports of high genomic diversity in P. vivax relative to the more virulent Plasmodium falciparum species; regional populations of P. vivax exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
267
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 180 publications
(297 citation statements)
references
References 50 publications
18
267
1
2
Order By: Relevance
“…As these species have emerged from the bottleneck, they likely have undergone both sustained and recent selection. In the case of P. vivax, previous work has demonstrated that long-term diversifying and directional selection has shaped its genetic diversity (63,68). Our data are consistent with this finding, showing minimal structuring in the P. vivax population but evidence of strong directional selection in multiple regions of the genome.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As these species have emerged from the bottleneck, they likely have undergone both sustained and recent selection. In the case of P. vivax, previous work has demonstrated that long-term diversifying and directional selection has shaped its genetic diversity (63,68). Our data are consistent with this finding, showing minimal structuring in the P. vivax population but evidence of strong directional selection in multiple regions of the genome.…”
Section: Discussionsupporting
confidence: 91%
“…However, we cannot rule out the possibility that other selective pressures have also affected parasite population structuring, for example, widespread deforestation and climate change altering the diversity of Anopheline vectors or evolving host-parasite interactions within mosquito vectors. In P. vivax, a strong New World vs. Old World divide correlates with genetic variation in pvs47, the ortholog of pfs47, which has been associated with differential infectivity in different mosquito species (63,64). However, both Anopheles dirus s.s. and Anopheles minimus s.s., the main malaria vectors in Cambodia, are adept at transmitting both P. falciparum and P. vivax (65,66).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SRP081144). At the nuclear level, the American isolates show geographic differentiation but also a common clustering regarding the Old World populations (5).…”
Section: Significancementioning
confidence: 99%
“…For example, the current global distribution of P. vivax includes Asia, the Middle East, South and Central America, and parts of Africa (3) and has likely resulted from complex dispersals involving intercontinental human population movements (4,5). Although an African origin is likely (6), the current strains from this continent show little genetic polymorphism compared with the rest of the world (4), a fact that has been related to the emergence of Duffy-negative blood types-resistant to P. vivax-in human populations from this continent (7).…”
mentioning
confidence: 99%